Enhancement of morphine-induced antinociception after electroconvulsive shock in mice. (February 2021) - Iwata, Ken; Takamatsu, Yukio; Doi, Nagafumi; Ikeda, Kazutaka
Electroconvulsive therapy (ECT) has been applied for chronic pain for decades. The amounts of opioids to treat pain are sometimes reduced after a series of ECT. The effect of ECT on morphine-induced analgesia and its mechanism underlying the reduction of morphine requirement has yet to be clarified. Therefore, we administered electroconvulsive shocks (ECS) to mice and investigated the antinociceptive effect of morphine in a hot plate test. We examined the expression level of µ-opioid receptor in the thalami of mice 25 h after administration of ECS compared to the thalami of mice without ECS administration using western blotting. ECS disturbed the development of a decrease in the percentage of maximal possible effect (%MPE), which was observed 24 h after a morphine injection, when ECS was applied 25, 23, 21, and 12 h before the second administration of morphine. We also examined the effect of ECS on the dose-response curve of %MPE to morphine-antinociception. Twenty-five hours after ECS, the dose-response curve was shifted to the left, and the EC50 of morphine given to ECS-pretreated mice decreased by 30.1% compared to the mice that were not pretreated with ECS. We also found that the expression level of µ-opioid receptors was significantly increased after ECS administration. These results confirm previous clinical reports showing that ECT decreased the required dose of opioids in neuropathic pain patients and suggest the hypothesis that this effect of ECT works through the thalamus.